2014
DOI: 10.1002/ijop.12080
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of hypothetical bereavement and grief: The influence of loss recency, loss type and gender

Abstract: Individuals often hold strict and erroneous expectations for how others should grieve, yet this issue has been sparsely researched. A total of 161 undergraduates rated the appropriateness of various social and emotional behaviours of a hypothetical bereaved individual as a function of the recency of the death (1 month or 1 year ago), the nature of the loss (death of a spouse or child) and the gender of the bereaved. As expected, subjects deemed it inappropriate to show positive emotions and experiences 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, the current study’s results are limited to attributes of spousal bereavement as spousal loss may produce differences in social attributions compared with other types of losses. Other studies have found that loss of a child was less negatively judged than loss of a spouse (e.g., Miller, 2015).…”
Section: Limitationsmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, the current study’s results are limited to attributes of spousal bereavement as spousal loss may produce differences in social attributions compared with other types of losses. Other studies have found that loss of a child was less negatively judged than loss of a spouse (e.g., Miller, 2015).…”
Section: Limitationsmentioning
confidence: 89%
“…Women are more likely to use emotion-focused coping (Bennett et al., 2010) and may be judged as interpersonally attractive if high-intensity grief is expressed after the death of a loved one (Kubitz et al., 1989). Despite studies indicating gender differences in grief expression and coping after a loss, recent studies have found that social expectancies for male and female grievers are the same (Miller, 2015; Penman et al., 2014). However, raters indicated that they would be more likely to interact with a bereaved woman regardless of type of death (stroke or car crash) than a bereaved man (Penman et al., 2014).…”
Section: Key Factors Comprising the Myths Of Coping With Lossmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies significantly support that sex differences related to types of traumatic exposure influence posttraumatic coping [ 10 , 12 , 43 46 ]; however, events assessed in those studies – sexual abuse [ 6 , 7 , 9 ], domestic violence [ 10 ], exposure to war [ 17 20 ] or disasters [ 21 , 44 , 47 ] – not only are different than those considered in our sample, but also carry a specific quantitative (different rates in men and women) and qualitative posttraumatic impact (certain types of traumatic events carry different meanings in men versus women) [ 2 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 80%